Fenomenologis Spiritualitas pada Lansia di Panti Al-Hikmah - Maulida Kholifaqurrozi; Lisanul Faidah; Dhiya' Fairuz Nabilah; Muhammad Anas Al Irsyad; Rahmadhani Dwi Muryani; Annisa Arya Ramadhanti; Aldhi Trinanda Hendrawan; Muhammad Juna Athalla Syah; Afrida Chaerunissa; Siti Hikmah Anas (Lembaga Pengembangan Kinerja Dosen, 2025)
Old age is a phase of life that is full of challenges, especially for elderly people living in social institutions who experience limitations in social relationships and emotional support. In the midst of these conditions, spirituality becomes an important aspect that is believed to be able to provide inner peace and meaning in life. This study aims to explore the spiritual experiences of elderly people in making sense of their lives at the Al-Hikmah Elderly Care Home. The approach used is qualitative phenomenological, with five elderly participants selected through purposive sampling. Data collection was conducted through in-depth interviews with semi-structured guides and analyzed using thematic methods. The results of the study indicate that spirituality is broadly interpreted, encompassing acceptance of life, strengthening of moral values, transcendental experiences, and personal closeness to God. This spiritual process fosters psychological strength, helping the elderly cope with physical and social limitations with greater calmness and meaning. These findings emphasize the importance of integrating the spiritual dimension into psychosocial support for the elderly to enhance their quality of life holistically.